The controversy between Frege and Hilbert - Fernández de Castro, Max (Universidad de Costa Rica, 2018)
In this paper, I shall focus my attention on two subjects of the debate between Frege and Hilbert held around 1900 concerning the foundations of geometry: a) the difference between axioms and definitions, b) the proofs of independence of axioms. Concerning the first point, I will hold that Hilbert and Frege had different conceptions of ‘concept’ and that Hilbert’s position is problematic. Later, I shall explore Patricia Blanchette’s interpretation that Frege’s objections to Hilbert’s proofs of consistency and independence arise from his different notions of logical consequence. I will suggest that this interpretation is not correct, even if it fits well with most of the textual evidence, because it gives rise to certain puzzling consequences.